Increased variation in sex organ positions can increase reciprocity and pollination success in heterostylous plant populations. Issue 3 (20th April 2021) - Ganguly, Shatarupa; Shreenidhi, PM; Barua, Deepak
Abstract: The reciprocal position of sexual organs in complementary floral morphs is central to our understanding of heterostyly. Reciprocity indices are used to quantify the spatial match between complementary sex organs, but previous indices fail to appropriately account for intra‐population variation in sex organ positions. In this study, we examine how an increase in intra‐population variation in sex organ heights affects reciprocity and consequently reproductive success. We formulated a reciprocity index that incorporates this variation and asked if estimates of reciprocity can predict reproductive success in naturally occurring heterostylous populations. We developed a reciprocity index that assumed pollen transfer success equalled one for a perfectly matched stigma–anther pair, and decreased to zero with increasing mismatch. We examined the relationship between intra‐population variation in organ position and reciprocity, compared previously proposed indices using simulated populations and empirical data from natural populations, and tested the ability of the indices to predict reproductive success. We observed that when differences between mean complementary sex‐organ heights are small, increasing intra‐population variation in heights resulted in a decrease in reciprocity. However, when this difference is larger, reciprocity increased, reached a peak, and then decreased with increasing variation. Previous indices failed to capture this behavior. Seed set was positively related to reciprocity for our index. These results challenge the current understanding that increasing variation in sex‐organ heights will always decrease reciprocity in heterostylous populations. This may help explain why heterostylous systems exhibit and tolerate high amounts of intra‐population variation in sex organ heights. Abstract : Reciprocity indices are used to quantify the spatial match between complementary sex organs of heterostylous species, but previous indices fail to appropriately account for intra‐population variation in sex organ positions. In this study, we examine how an increase in intra‐population variation in sex organ heights affects reciprocity and consequently reproductive success. Challenging the current understanding, our results reveal that an increase in variation in sex‐organ heights can increase reciprocity in heterostylous populations. This may help explain why heterostylous systems exhibit and tolerate high amounts of intra‐population variation in sex organ heights. ​